Development Instrument of Interdisciplinary Thinking Skills in Science Lesson Planning (IITSSL) - Santiani Santiani; Winarto Winarto; Sri Jumini; Nadhrah Md Yatim (Tadris Ilmu Pengetahuan Alam (Natural Science Education) Study Program, Institut Agama Islam Negeri (IAIN) Kudus, Indonesia, 2024)
Non-Indexed Publication